PENGARUH PENGELOLAAN LIMBAH DAN BIAYA LINGKUNGAN TERHADAP KINERJA LINGKUNGAN DENGAN PERTANGGUNGJAWABAN SOSIAL SEBAGAI PEMODERASI - Fajar Fajar; Raodahtul Jannah (JAKA - Jurnal Jurusan Akuntasi, 2023)
The purpose of this research is to determine the influence of waste management and environmental costs variables on environmental performance variables, as well as the interaction of social accountability variables. The population in this study includes accountants, assistant accounting managers, production department employees, financial accounting admins, and the general public. The sample selection technique used purposive sampling method with a total of 33 individuals. The data used in this research are primary data collected through direct questionnaire surveys. The questionnaire results have been tested for validity and reliability, and classical assumption tests such as normality test, multicollinearity test, heteroskedasticity test, and autocorrelation test have been conducted. The hypothesis testing method involves multiple linear regression analysis, and the statistical analysis is performed using the SPSS application. The research results indicate that waste management and environmental costs significantly influence (positive) environmental performance. Multiple linear regression analysis and statistical analysis show that the social accountability variable is unable (negative) to moderate the influence of waste management, while it is able to moderate (positive) the influence of environmental costs on environmental performance. The implications of this research are that respondents can consider and understand variables that have the potential to have positive and negative influences on generating social accountability. Even though social accountability does not affect the influence of waste management on environmental performance, it should still be considered to maintain environmental sustainability and compliance with social accountability.